2017
DOI: 10.1080/15205436.2017.1381262
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Intergroup Emotions: An Intergroup Threat Theory Approach

Abstract: The current study tests whether media consumption is associated with negative intergroup emotions toward Blacks, Latinos, and Asians and whether media use indirectly influences intergroup emotions via threat perceptions. We do so, using a two-study survey design. Results from Study 1 indicate that media consumption is associated with anger toward Latinos and Asians, but not anger towards Blacks. We also found that media use was associated with anxiety towards Blacks, Latinos, and Asians. Results from Study 2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
0
11
1
1
Order By: Relevance
“…Our findings provide an answer by showing that cultivation effects are prevalent on Facebook, but the cultivation variables differ in respect to the distance to media audience's social environments and in relation to the nature of effects. In contrast to the rather negatively connoted cultivation effects of media exposure to ethnic minorities found by prior research, for instance, intergroup threat perceptions and emotions (Atwell Seate et al , 2018), our studies revealed positive cultivation effects. That is, Facebook conveys to users a reality that is ethnically diverse, which, in turn, positively influences ethnic diversity perceptions and attitudes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings provide an answer by showing that cultivation effects are prevalent on Facebook, but the cultivation variables differ in respect to the distance to media audience's social environments and in relation to the nature of effects. In contrast to the rather negatively connoted cultivation effects of media exposure to ethnic minorities found by prior research, for instance, intergroup threat perceptions and emotions (Atwell Seate et al , 2018), our studies revealed positive cultivation effects. That is, Facebook conveys to users a reality that is ethnically diverse, which, in turn, positively influences ethnic diversity perceptions and attitudes.…”
Section: Discussioncontrasting
confidence: 99%
“…In light of the negative influence of TV consumption on attitudes toward ethnic minorities and immigration proved by extant research (e.g. Atwell Seate et al , 2018; Czymara and Dochow, 2018), future studies should additionally control for TV exposure (overall and genre-specific) when investigating the cultivation effects of Facebook use. Thereby, the understanding of cultivation effects of different media vehicles and their interplay can be advanced, and individual differences in media use (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This research indicates that exposure to intergroup threat in the media can encourage intergroup contempt (which is associated with avoidance and exclusion behaviors), prompting restrictive policy preferences, and information sharing in support of such preferences (Atwell Seate & Mastro, 2017). Similarly, TV consumption has been found to be associated with increased group-level anger toward racial/ethnic groups in the United States (Atwell Seate et al, 2018). Finally, although not directly testing IET, Ramasubramanian (2010) found that group-based emotions prompted by television use, mediate the influence of cognitions on group-level attitudes and policy positions.…”
Section: Ietmentioning
confidence: 99%
“…These policies included three-strikes legislation, the death penalty, decreased support for Black crime victims, and increased anti-Black sentiment (Dukes & Gaither, 2017). Other media stereotyping scholars found that daily television consumption among largely White samples cultivates anxiety towards Asians (Atwell Seate, Ma, Chien, & Mastro, 2018).…”
Section: Theories and Effects Of Mediated Stereotypesmentioning
confidence: 99%